多尺度主元坐标变换在轴承故障声发射信号增强检测中的应用 - 张晓涛; 唐力伟; 王平; 邓士杰 (Jixie chuandong)
Aiming at the problem of weak feature extraction and recognition in the bearing acoustic emission signal processing,multi-scale principal component coordinate transformation is proposed to enhance fault feature.Firstly,the signal is decomposed by wavelet package,and the sub-band reconstruction component is converted to a new linear space by principal component analysis,and the signal fault feature is enhanced.Finally,the method performance is verified by simulation signal and testing signal,the results show that multi-scale principal component coordinate transformation has obvious enhancement effect in bearing fault detection.